1995
DOI: 10.1063/1.113661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poling on piezoelectric properties of lead zirconate titanate thin films formed by sputtering

Abstract: Lead zirconate titanate (PZT) thin film was formed on Pt/Ta/Si3N4/Si(100) substrate at 400 °C by sputtering and then annealed at 650 °C in air. The PZT film was 1 μm thick and had dielectric permittivity of 980, loss tangent of 0.05, remanent polarization of 31 μC/cm2, and coercive field of 110 kV/cm. Piezoelectric property of the film formed on silicon cantilever was estimated from the converse effect. Poling at 5 kV/mm increased the property by a factor of 1.2 to 3.4, resulting in converse piezoelectric cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…The elastic properties of solid films can hence be significantly different from those of their bulk counterparts. The Young's modulus of 0925 PZT material has been reported to range from 37 GPa [24] to 400 GPa [25]. It should be careful when using elastic constants of the bulk PZT material in calculating XEC of PZT thin films.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic properties of solid films can hence be significantly different from those of their bulk counterparts. The Young's modulus of 0925 PZT material has been reported to range from 37 GPa [24] to 400 GPa [25]. It should be careful when using elastic constants of the bulk PZT material in calculating XEC of PZT thin films.…”
Section: Introductionmentioning
confidence: 99%
“…The poling is accomplished by applying an electric field across the material at elevated temperatures; for thin films, longer poling times are typically required compared to bulk ceramics [24,25].…”
Section: Electricalmentioning
confidence: 99%
“…Another important issue of PZT is its superior brittleness [23], representing a strong limitation in view of the development of mechanical flexible transducers conformable to structural surfaces. Moreover, PZT transducers require an additional poling treatment in order to induce the alignment of ferroelectric domains and to promote the emergence of piezoelectricity [24]. In order to overcome some of these limitations the use of flexible, low-cost PE polymers took place and different works demonstrated that poly(vinyledenefluoride) (PVDF) and its copolymer poly(vinylidene fluoride-trifluoroethylene) (PVDF-TrFE) could be good alternatives to brittle piezoceramics.…”
Section: Introductionmentioning
confidence: 99%